Review—Recent Advance in Multi-Metallic Metal Organic Frameworks (MM-MOFs) and Their Derivatives for Electrochemical Biosensor Application. Issue 1 (14th January 2022) - Rezki, Muhammad; Septiani, Ni Luh Wulan; Iqbal, Muhammad; Adhika, Damar Rastri; Wenten, I Gede; Yuliarto, Brian
Abstract : The recent trend on metal organic framework (MOF) studies has shifted to the development of MOFs with many metal nodes, also known as multi metallic MOF (MM-MOF). Many studies have shown that MM-MOF display much better performance compared to single metallic MOFs. In addition, derived MM-MOF products such as metal hybrids, MM-MOF composites, and MOF-on-MOF also provide interesting unique characteristics. In this review, we summarize the synthesis strategy of MM-MOF and their derivates in three different approaches, including one-pot synthesis/direct mixing, post-synthesis modification, and MOFs derivative preparation. In many applications, such as cancer markers detection, diabetic disease detection, metabolic disease detection, infectious disease detection, and toxic pollutant detection, MM-MOF based biosensors displayed excellent sensing performance as well as stability, selectivity, and reproducibility. This review provides a point of view on the recent development, preparation, and application of MM-MOF including the challenge and future prospect of this material.